Synthesis, Stability Constants and Thermodynamic Parameters of Binary Complexes of Di(2-chlorophenyl) Carbazone - Siddalingaiah, A.H.M.; Kariduraganavar, M.Y. (Asian Journal of Chemistry, 2010)
The ligand di(2-chlorophenyl) carbazone (DOCIPC) has been synthesised for the first time and characterised by melting point, thin layer chromatography, elemental analysis, mass, 1H NMR and IR spectra. Stability constants of the complexes of Mn(II), Co(II), Cd(II), Zn(II) , Cu(II), Ni(II) and Fe(II) with DOCIPC have been determined potentiometrically in 50% (v/v) aqueous-dioxane at an ionic strength of 0.1 M NaClO4 and at different temperatures. The method of Bjerrum and Calvin, as modified by Irving and Rossotti, has been used to find out the values of n and ρL . The stability constants have been calculated using a PC–XT computer by the weighted least squares method. The stability constants have also been calculated by Bjerrum half n method. The order of stability constants is found to be: Mn(II) < Co(II) < Cd(II) < Ni(II) < Zn(II) < Fe(II) < Cu(II). Thermodynamic parameters, ΔG, ΔH and ΔS have been calculated.